2017
DOI: 10.1504/ijsa.2017.085322
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aircraft engine performance and emission analysis using alternative fuels

Abstract: Abstract:Following the successful flights of many commercial aircraft running with alternative fuels, the present study focuses on aircraft engine performance and emission analysis. The analysis of aircraft engine performance (thrust, fuel flow and specific fuel consumption) for different blended mixing ratio percentages of biofuels (Camelina and Jatropha) with Jet-A, at different flight conditions using in-house computer software codes, PYTHIA and TURBOMATCH. Emission analysis utilised HEPHAESTUS in-house sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Compared to Camelina biofuel, the pure jatropha biofuel gave better thrust and lower SFC and fuel flow due to the low heating value. On the other hand, the lowest NOx emissions were for 50% jatropha biofuel blended with jet fuel at all flight conditions [21].…”
Section: Application Of Biofuel In Gas Turbinesmentioning
confidence: 89%
“…Compared to Camelina biofuel, the pure jatropha biofuel gave better thrust and lower SFC and fuel flow due to the low heating value. On the other hand, the lowest NOx emissions were for 50% jatropha biofuel blended with jet fuel at all flight conditions [21].…”
Section: Application Of Biofuel In Gas Turbinesmentioning
confidence: 89%
“…• As part of the alternative fuels, few studies are found on liquid hydrogen fuels in commercial aviation, and investigating how it compares to kerosene is essential to the regulatory process as well as to investments in biofuels (Azami et al, 2017;Rondinelli et al, 2017;Balli et al, 2021a).…”
Section: Future Researchmentioning
confidence: 99%
“…In research by Abrahamson et al, 23 a model is presented to predict black carbon mass emissions in cases of conventional and alternative aviation fuel consumption during ground and flight operations. In Azami et al, 24 emissions characteristics of alternative fuels are presented in addition to engine performance analyses. It is concluded from the study that it is possible to reduce the nitrogen oxide emissions consumption of pure Jatropha biofuel with regard to conventional aviation fuel, whereas carbon monoxide emissions are highly dependent on combustor inlet conditions and phases of flight.…”
Section: Introductionmentioning
confidence: 99%